Notes on Encoding Ethiopic for LATEX - Beyene, Berhanu; Kudlek, Manfred; Kummer, Olaf (Aethiopica, 2000)
Encoding Ethiopic for computer application is increasingly important for linguists, librarians, information and communication technologists. This paper focusses on encoding Ethiopic for the LATEX document preparation system, and on the methods and principles of the ethiop package which supports Ethiopie for LATEX. ethiop is a package developed by a research group at the University of Hamburg, that integrates Ethiopic to the TEX/LATEX system. We hope that this package opens up a new venue to scientific and mathematical document processing, using the rich and well developed TEX/LATEX system. Moreover, it could render a better data exchange mechanism by virtue of its platform independence and plain ASCII nature.